DEVELOPMENT OF STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATIC) INTEGRATED CHEMICAL MODULE ON VOLTAIC CELLS - Diah Nurma Asih; Imas Eva Wijayanti; Indah Langitasari (Jurnal Tadris Kimiya, 2020)
21st century requires generation to have high competitiveness and competence in various aspect. Moreover,challenges in the teaching and learning process on chemical subjects, such as voltaic cells, which has abstract and contextual characteristics, as a problem to be solved. This study aimed to produce an integrated chemical module STEM Project Based Learning on the topic of valid and practical voltaic cells. The development of STEM integrated chemical module on the topic of the Voltaic cell used ADDIE model namely Analyze, Design, Development, Implementation and Evaluation. Data was collected through needs analysis, expert testing and student questionnaire responses. At the expert review stage, using 7 material experts and 7 media experts. The implementation phase was carried out in one of the high schools in Serang City. The result of the expert test stage obtained a final score of material validation of 88.25% (very feasible or very valid) and media validation of 82% (very feasible or very valid) with an average score of validity of 87% (very feasible or very valid). For the final score of feasibility obtained from 81% limited trials (very feasible). The characteristics of the developed module was STEM module which follows the Laboy-Rush PjBL-STEM syntax namely refelection, research, discovery, application, and communication. It was made by A5 paper size to make it easy to carry and prepared by various illustrations, interesting features and STEM-Project and design log to complete Voltaic cell project. Furthermore, it is hoped that this module can be used as an alternative STEM teaching material on voltaic cell topic.